The Future of Saudi Arabia’s Date Exports Using a Cointegration Model - Alnafissa, Mohamad; Alderiny, Mahmoud; Alamri, Yosef; Alhashim, Jawad (Asian Journal of Agriculture and Rural Development, 2021)
Dates represent an important export crop for Saudi Arabia that attracts foreign exchange. There is an opportunity for Saudi Arabia to extend its date exports to the international market due to production exceeding consumption and comparative advantage in date production. This paper explores the future export market for Saudi dates by analyzing the factors that affect Saudi date exports and highlighting this crop’s comparative advantage. Also, the paper uses autoregressive and distributed lag methodology with data from 1980 to 2017 to predict the future for exported dates between 2020 and 2025. The relationship between the export of dates and other exogenous variables shows there are significant effects from domestic production, domestic consumption of dates, and the price of exported dates in both the long and short term. In contrast, the comparative advantage of Saudi dates shows a significant effect only in the short term, because there has been no active program to promote Saudi dates in global markets. The explanatory variables predict that 2019 Saudi date exports will increase by 3.8-fold in 2025, with the total export amount over 700 thousand tons. Thus, there is an opportunity to develop more programs that target the international market in support of date farms and exporters, and to support market research directed at satisfying the international market.